Incomplete Immunization and Chronic Energy Deficiency (CED) as Risk Factors for Stunting in Toddlers - Ananda Hafid Firdausi; Mohammad Shoim (Disease Prevention and Public Health Journal, 2023)
Background: Stunting is a problem caused by long-term malnutrition so that at the age of 24-59 months the physical manifestations are more visible. Completeness of immunization and nutritional status of pregnant women are aspects that are risk factors for stunting. The prevalence of stunting in 2020 in the world reached 22%, while in Indonesia it is 30.8%. The purpose of this study was to analyze the relationship between the completeness of immunization and the nutritional status of pregnant women with the incidence of stunting in children under five aged 24-59 months. Method: The research method with this type of observational analytic research is a case-control approach. The sample size is 178, the sample is taken by purposive sampling, using secondary data obtained at the Wilangan Health Center. Results: Based on the chi-square test, it was found that there was a relationship between the completeness of immunization and the incidence of stunting with a value of p<0.001 (OR=12.63) and there was a relationship between the nutritional status of pregnant women and the incidence of stunting with a value of p<0.001 (OR=13.58). The results of the logistic regression test analysis showed a p-value <0.001 on the completeness of immunization and nutritional status of pregnant women for stunting with OR values of 5.71 and 5.52 respectively. Conclusion: There is a significant relationship between the completeness of immunization and the nutritional status of pregnant women with the incidence of stunting.